Makna Referensial Pada Komik Bahasa Arab Nawâdhîr Jûhâ Li al-Athfâl - Hidayah, Reni Lailina (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2021)
This qualitative descriptive study aims to describe the referential meaning contained in the Arabic comic Nawadhir Juha li al-Athfal, and to explain the referential meaning in the Arabic comic Nawadhir Juha li al-Athfal. The data in this study are in the form of writings that can be extracted from the referential meaning of the Arabic comic Nawadhir Juha li al-Athfal. The data collected in this study used the reading and note technique method with the data analysis technique using the intralingual and extra lingual matching methods. The matching method is followed by the basic technique of Sorting Determining Elements. The theory used is the theory of meaning Ferdinand De Saussure. The results of the analysis in this study are that there are eighteen referential meanings in the comic Nawadhir Juha li al-Athfal.